Prevalence of major foliar and panicle diseases of Sorghum (Sorghum bicolor [L.] Moench) in the Deccan Plateau of India - Navi, S.S.; Bandyopadhyay, Ranajit; Tonapi, V.A.; Rao, T.G.N.; Indira, S.; Reddy, R.K.; Thomas, D. (Informa UK Limited, 2007)
Extensive on-farm disease surveys were conducted from August 1999 until March 2001 in four sorghum-growing states of the Indian Deccan plateau. A total of 965 fields were surveyed covering 228 fields in Andhra Pradesh (AP), 406 in Karnataka (KAR), 290 in Maharashtra (MH) and 41 in Tamil Nadu (TN). Among 14 foliar diseases observed, maize stripe virus (MStV), a tenuivirus transmitted by the delphacid plant hopper (Peregrinus maidis), and among five panicle diseases, ergot or sugary disease (Claviceps sorghi and C. africana) were the most destructive diseases. MStV was prevalent in 28.4% and ergot in 13.4% of the fields surveyed in two years across four states. Yet, the mean incidence of MStV in AP was 6% with 85% mean severity. The values in KAR were 12% incidence and 83% severity, in MH 5% and 67%, and in TN 12% and 76%, respectively. The mean incidence of ergot in AP was 34% with 67% mean severity. The values in KAR were 41% and 79%, in MH, 30% and 67%, and in TN 100% and 100%, respectively. Variation in frequency of occurrence of MStV was observed between 1999 and 2001. Variations in frequency could be due to weather factors, vector survival, cropping pattern, and host specificity. The frequency of ergot also was varying among years, locations, seasons and cultivars. An ergot epidemic was observed during the 1999 rainy season in Maachinenipalli village (16°35′N; 78°3′E), Andhra Pradesh. In September 2000, the disease had spread to 13 neighboring administrative zones damaging about 130,000 ha. This paper elucidates the distribution of diseases observed between 1999 and 2001 but does not imply that the diseases are restricted necessarily to a particular zone or location.